Triazole induced changes on biochemical and antioxidant metabolism of Zea mays L. (Maize) under drought stress - Gabriel Amalan Rabert, Paramasivam Manivannan*, Mahalingam Rajasekar, (Journal of Plant Stress Physiology, 2015)
The effects of triazole compounds namely triadimefon (TDM), tebuconazole (TBZ), and propiconazole (PCZ) on drought stress, biochemical, and antioxidant metabolism were studied in Zea mays L. (Maize) under pot culture. Plants were subjected to 4 days interval drought stress and drought with TDM at 15 mg/L, TBZ at 10 mg/L, and PCZ at 15 mg/L separately by soil drenching on 30, 40, and 50 days after sowing (DAS). Irrigation at 1 day interval was kept as control. The plant samples were collected on 40, 50, and 60 DAS and separated into root, stem, and leaf for estimating the amino acid (AA) and proline (PRO) contents and the activities of antioxidant enzymes. The drought and drought with triazole treatments increased the AA and PRO contents, superoxide dismutase, catalase, and ascorbate peroxidise activities when compared to control. Our results of this investigation have good significance, as this increase the innate biochemical and antioxidant metabolism of this maize plant.